Multilevel authentication scheme for security critical networks. Issue 1 (2nd January 2018) - Dinker, Aarti Gautam; Sharma, Vidushi; Mansi,; Singh, Neeta
Abstract: The global use of smart electronic devices has given rise to new security and privacy concerns. The attacker can launch any security attacks by using a person's Smartphone which can threaten the security of that person and other network users. Several security mechanisms were designed with the goal of secure authentication of the user, nonstop and indirectly by using sensors like accelerometer, magnetometer, and orientation sensor, face capture with gyroscope or by password pattern, other biometric authentication methods and give alerts whenever required. In this paper, we introduce an explicit and implicit authentication approach that secures not only smart phones but can secure other electronic devices that needs greater level of safety from attackers. User authorization is an important security measure for protecting the information stored on any other electronic device, as these devices have a high risk of theft or unauthorized access. In this paper we provide multiple security checks in three steps to form a strong authentication and authorization framework for electronic devices other than smart phones. The three level authentication method used is involves password, a biometric authentication method and final security check using accelerometer.